Overview of Nasal masses - Pradhananga, RB; Adhikari, P; Thapa, NM; Shrestha, A; Pradhan, B (Journal of Institute of Medicine Nepal, 2009)
Background: This study was performed to determine distribution of various nasal masses and correlate between clinical and histopathological diagnosis. Methods: A prospective study of 143 cases of nasal masses were done in patients of > 13 years undergoing surgery over 2 years period (Apr.2004 to Apr.2006). All the patients with suggestive symptoms were examined and diagnosed clinically. All the patients were posted for surgical treatment and the specimens were sent for histopathological examination postoperatively, and reports were noted. The age and sex distribution with patients of various nasal masses and correlation between clinical and histological diagnosis also were analyzed. Results: There were 78 male and 65 female operated for nasal masses. Among the nasal masses operated, the commonest was the ethmoidal polyps (53 patients, 37.06%). The ethmoidal polyps, polyps, bleeding polypus of septum and fungal polyps were common in age group of <40 years whereas inverted papilloma and malignancy were common in >40 years. The ethmoidal polyps and AC polyps were common in male whereas bleeding polypus of septum were in female. A case of venous haemangioma (histopathology) was clinically diagnosed as angiofibroma. In one clinically suspected case of ethmoidal polyps was reported as inverted papilloma. Similarly clinically diagnosed five cases of inverted papilloma were histopathologically reported as inflammatory polyps in two, angiofibroma in one and Squamous cell carcinoma in two cases. Conclusion: The commonest nasal masses operated was ethmoidal polyps. A discrepancy between the pre-operative clinical diagnosis and final histopathological diagnosis was found in 6.3% of the patients. Key words: nasal masses, ethmoidal polyps, AC polyps The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 13-16